View-based Modelling and State-Space Generation for Graph Transformation Systems - Arijo, Niaz; Heckel, Reiko (Electronic Communications of the EASST, 2012)
Modelling complex systems by graph transformation, we face scalability challenges both in our ability to create and understand these models and in the ability of tools to analyse them. To address these problems we propose to model graph transformation systems in views which can be understood and analysed separately. In particular, we show that transition systems can be generated separately for different views which, when synchronised using a CSP-like operator, yield a system that is bisimilar to the original global system.